HUBUNGAN SIKAP KERJA TIDAK ALAMIAH TERHADAP MUSCULOSKELETAL DISORDERS PADA PEKERJA MANUAL HANDLING - Bayu Sela Priyatna; Heri Sugiarto; Karunia Agustin (JURNAL KESEHATAN INDRA HUSADA, 2022)
Cases of Musculoskelatal Disorders (MSDs) caused by work that was too forced in the lifting process totaled 356,910 cases or 31% of all workplace accident cases. Studies on MSDs in various types of industries have been carried out and the results of the studies show that the parts of the skeletal muscles which include the muscles of the neck, shoulders, arms, hands, fingers, back, waist and lower muscles, complaints in the parts of the skeletal muscles that are often experienced by workers, especially Manual Handling or hauling workers in the sense that there is a significant relationship between MSDs complaints and work posture in manual handling workersThis research method uses Literature Review or literature review with a Systematic Literature Review approach by searching articles through search engines such as Google Scholar and DOAJ. The keywords used to search for articles include unnatural work attitudes (work posture) with MSDs, in selecting articles using inclusion criteria and journal analysis. The results of the Literature review study of 7 journals were obtained and stated that there was a relationship between work attitude and MSD complaints in manual handling workers.